2003
DOI: 10.1046/j.1365-2109.2003.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Heritabilities and genetic correlations of size traits at harvest size in sexually dimorphic Pacific white shrimp (Litopenaeus vannamei ) grown in two environments

Abstract: A captive population of Paci¢c white shrimp (Penaeus vannamei) replicated in two environments was evaluated for genetic variability and covariability of size traits. A total of 37 full-sib families, each with an average of 16^20 individuals within family, were used for the analysis. There was no family by environment interaction for any of the traits. However, both ¢xed effects, sex and environment, were signi¢cant. The shrimp grown in environment 'B' (Sinaloa) grew larger and heavier than those grown in envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 13 publications
4
48
1
1
Order By: Relevance
“…The results show that genetic correlations were higher than phenotypic correlations and that the two growth periods were similar. Similarly, Pérez-Rostro et al (2003b) reported high genetic correlations between growth-related traits (ranging from 0.44 to 0.98) compared with those reported previously for P. vannamei, but the phenotypic correlation was higher than the genetic correlation, which differs from our findings, the proper reason was environment effects covered up genetic correlation in our study. A high positive phenotypic and genetic correlation for growth-related traits has been observed for other shrimp species, such as M. rosenbergii (Hung et al 2014;Kitcharoen et al 2012;Hung et al 2013), as well as different fish species (McKay et al 1986;Myers et al 2001;Silverstein & Hershberger 1994).…”
Section: Phenotypic and Genetic Correlationscontrasting
confidence: 57%
“…The results show that genetic correlations were higher than phenotypic correlations and that the two growth periods were similar. Similarly, Pérez-Rostro et al (2003b) reported high genetic correlations between growth-related traits (ranging from 0.44 to 0.98) compared with those reported previously for P. vannamei, but the phenotypic correlation was higher than the genetic correlation, which differs from our findings, the proper reason was environment effects covered up genetic correlation in our study. A high positive phenotypic and genetic correlation for growth-related traits has been observed for other shrimp species, such as M. rosenbergii (Hung et al 2014;Kitcharoen et al 2012;Hung et al 2013), as well as different fish species (McKay et al 1986;Myers et al 2001;Silverstein & Hershberger 1994).…”
Section: Phenotypic and Genetic Correlationscontrasting
confidence: 57%
“…Genetic improvement programmes can increase the economic efficiency of farmed shrimp (Argue, Arce, Lotz & Moss ; Pérez‐Rostro & Ibarra ,b; Gitterle, Rye, Salte, Cock, Johansen, Lozano, Suárez & Gjerde ; Gitterle, Salte, Gjerde, Cock, Johansen, Salazar, Lozano & Rye ; Castillo‐Juárez, Casares, Campos‐Montes, Villela, Ortega & Montaldo ; Andriantahina, Liu & Huang ; Campos‐Montes, Montaldo, Martínez‐Ortega, Jiménez & Castillo‐Juárez ). Selective breeding programmes have been conducted for several species, including Fenneropenaeus chinensis (Zhang, Kong, Luan, Wang, Luo & Tian ), Penaeus monodon (Kenway, Macbeth, Salmon, McPhee, Benzie, Wilson & Knibb ; Krishna, Gopikrishna, Gopal, Jahageerdar, Ravichandran, Kannappan, Pillai, Paulpandi, Kiran, Saraswati, Venugopal, Kumar, Gitterle, Lozano, Rye & Hayes ; Sun, Huang, Jiang, Yang, Zhou, Zhu, Yang & Su ), Penaeus japonicas (Hetzel, Crocos, Davis, Moore & Preston ), Oreochromis niloticus (Charo‐Karisa, Komen, Rezk, Ponzoni, van Arendonk & Bovenhuis ) and Macrobrachium rosenbergii (Luan, Wang, Yang, Luo, Chen, Gao, Hu & Kong ).…”
Section: Introductionmentioning
confidence: 99%
“…Larvae production and juvenile rearing of the 102 families were done as described by Perez-Rostro and Ibarra [14]. In short, each family was grown in an individual 100-L tank from nauplii to postlarvae 15-day old (PL15), using an initial stocking density of 100 naupliiAEL…”
Section: Production Of the Familiesmentioning
confidence: 99%